Assessment of Platelet Indices Profile of Pregnant Women Attending University of Abuja Teaching Hospital, Nigeria - Amos Dangana; Anthony Uchenna Emeribe; Hezekiah Alkali Isah; Sanusi Musa; Joel Monday Abu; Solomon Oloche Onoja; Nkechi Onukegbe; Idris Nasir Abdullahi (Universitas Nahdlatul Ulama Surabaya, 2021)
Platelets initiate hemostasis by aggregating at the site of injury and participate in ensuring endothelial integrity. A defect in this process could lead to intravascular blood loss. This case-control study sought to determine the platelet counts and indices among pregnant women in the University of Abuja Teaching Hospital Gwagwalada, Abuja, Nigeria. A total of 120 pregnant women as case and 60 non-pregnant women as control were enrolled for this study. Blood samples were collected in EDTA tubes, and complete platelet count and indices were carried out using an automated five-part haematology analyzer. The mean ± standard deviation of the platelets count among the pregnant women, 226.54 ± 69.76 109 cells/L was not significantly different from that of the non-pregnant women, 214.95 ± 52.22x 109 cells/L (p=0.295). There was a significant differences in mean platelets volume (MPV) of the case and control groups (p=0.036). After post-hoc test, the significant difference was between the pregnant women in 3rd trimester and the control group (p=0.014). However, there was no diffences in the mena platelets larger cell ratio and platelet distribution width in the case and control groups. Fifteen (11.0%) and 7 (12.1%) of the case and control control groups, respectively had mild thrombocytopenia. However, there was no significant association between pregnant status and thrombocytopenia (p=0.836). Based on these findngs, it can be infered that platelet count and MPV decreases while PDW increase with the progression of gestation age compared to the non-pregnant women.